2012
DOI: 10.1158/1078-0432.ccr-11-3152
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies in the Treatment of Mantle Cell Lymphoma

Abstract: Mantle cell lymphoma (MCL) is a rare type of non-Hodgkin lymphoma that traditionally has been thought to possess the poor-risk features of both indolent lymphoma, with its incurability, and aggressive lymphoma, with its ability to proliferate rapidly. Although there is considerable debate as to whether MCL can be cured, a number of retrospective studies are beginning to suggest an improvement in overall survival over the past decade, likely coinciding with the introduction of rituximab, more intensive chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 122 publications
1
7
0
Order By: Relevance
“…The clinical course of MCL is characterized by an initial high response rate but a constant relapse pattern, resulting in a poor long-term outcome [2]. It has been reported that first-line chemotherapy including rituximab is associated with significantly improved survival in older patients diagnosed with MCL compared with chemotherapy alone [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The clinical course of MCL is characterized by an initial high response rate but a constant relapse pattern, resulting in a poor long-term outcome [2]. It has been reported that first-line chemotherapy including rituximab is associated with significantly improved survival in older patients diagnosed with MCL compared with chemotherapy alone [3].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that first-line chemotherapy including rituximab is associated with significantly improved survival in older patients diagnosed with MCL compared with chemotherapy alone [3]. In the last years, the proteasome inhibitor bortezomib and bendamustine, an hybrid drug between a nucleoside analog and an alkylating agent, have been approved in USA for the treatment of patients with relapsed MCL patients, either alone or in combination with rituximab [2]. Here, we observed an antagonistic effect between bortezomib and acadesine whereas for bendamustine we detected an additive or synergistic effect depending on the MCL cell line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Given the lower risk of causing transplant-related mortality, most centers prefer to use a reduced-intensity conditioning approach because cures after allogeneic transplantation occur not as a consequence of dose-intensive conditioning but rather are mediated by engrafting donor T cells that induce powerful and curative GVT effects. 3,5,9 Investigators recently reported excellent results after reduced-intensity transplants for relapsed MCL. By using a novel reduced-intensity regimen, Khouri et al 10 reported a 100-day mortality of 0%, a CR rate of 94%, a 3-year progression-free survival of 82%, and a median overall survival of 85% in patients with advanced/ recurrent MCL.…”
Section: Discussionmentioning
confidence: 99%